Normal Coordinate Analysis of 2,6-Diaminopurine - Krishnakumar, V.; Ramasamy, R. (Asian Journal of Chemistry, 2010)
The Fourier transform infrared spectrum of 2,6-diaminopurine was recorded. Normal coordinate analysis has been carried out by assuming Cs point group symmetry. Assignments to the observed bands are made. The potential energy distributions obtained in this study are also supporting the assignments.